Pemanfaatan Tandan Kosong Kelapa Sawit Sebagai Media Tanam Pembibitan Batang Bawah Karet dengan Metode Root Trainer - Atminingsih Atminingsih; Junaidi Junaidi; Mardiana Wahyuni; Eka Bobby Febrianto (Politeknik Negeri Lampung, 2020)
Root trainer technology can be an alternative for rubber plant nursery that have ease in transportation and distribution. Organic materials which are lightweight, porous, and contain nutrients are considered suitable for root trainer growing media. This research was carried out at Sungei Putih Research Center Greenhouse, Deli Serdang from January - May 2019. The research was arranged based on a Randomized Block Design (RBD) with 4 media combination treatments namely: top soil (P0), empty bunches and manure (P1), empty bunches and rice husks (P2), and empty bunches and solid decanters (P3). The results showed that the planting media did not have a significant effect on plant growth including stem diameter, plant height, and number of leaves, as well as the percentage of successful grafting. The treatment of oil palm empty fruit bunches and solid decanter gave better growth than other organic materials. The availability of empty bunches and solid decanter in North Sumatra is relatively abundant so that it can support rubber nurseries throughout the year.